Teaching the Russian Language as a Native at Elementary School: Problems and Ways of Their Solution - Natalya Y. Yashina (Publishing house "Sreda", 2020)
The relevance of studying the Russian language as a mother tongue for the formation of national identity, spiritual and moral values, and communication and speech skills in younger schoolchildren is reviewed in the article. The purpose of the article is to identify ways to overcome the problems of a substantive and methodical nature in teaching of the new subject "Native Russian Language" by primary school teachers. Methods. Methods of analyzing the content of the basic course of the Russian language, a generalization of pedagogical practice and research activities of the Primary Education Department of SBEI of SVE "Nizhny Novgorod Institute of the Education Development" on the problem of the formation of communication and speech skills in primary schoolchildren and the development of communicative competence of a teacher, allowed identifying priority tasks, substantive blocks, practice-oriented and regional orientation of the program of the subject. Results. As a result of the study, the feasibility of the national and cultural and regional nature of the content and effective technological methods are highlighted. It is concluded that taking into account the specifics of the program, correctly selected by teachers relevant and appropriate content of educational material that meet the needs of younger schoolchildren, as well as effective teaching methods and tasks, contributes to solving problems, awareness of the national identity of the Russian language, cultural traditions and spiritual values of their people by students, and preserving the linguistic diversity of our country.